Hubungan Konsep Diri dan Konformitas dengan Perilaku Merokok pada Anak di SD “X” Kab. Tangerang - Nur Aprilia, Elisha; Diel, M. Martono; Pratiwi, Ayu (Pustaka Galeri Mandiri, 2025)
Smoking behavior among elementary school-aged children is a concerning phenomenon as it can have negative impacts on physical health and psychosocial development. Self-concept and conformity are two psychological factors believed to play a role in promoting smoking behavior among children. Children with negative self-concepts and high levels of conformity are more susceptible to social pressure, including invitations to smoke. This study aims to investigate the relationship between self-concept and conformity with smoking behavior among children at SD “X” in Tangerang Regency. This study used a quantitative design with a cross-sectional approach. The sample consisted of 104 fourth and fifth-grade students who had smoked, selected using total sampling technique. The instruments used were questionnaires on self-concept, conformity, and smoking behavior. Data analysis was conducted using univariate and bivariate analysis with the Pearson Chi-Square test. Most respondents had a positive self-concept (51.0%) and moderate conformity (70.2%). The Pearson Chi-Square test results showed a significant relationship between self-concept and smoking behavior (p = 0.000), as well as a significant relationship between conformity and smoking behavior (p = 0.000). This study shows that self-concept and conformity are related to smoking behavior among children at SD “X” in Tangerang Regency, where a negative self-concept and high conformity increase the likelihood of smoking. Therefore, active involvement from schools and parents is needed to foster a positive self-concept and prevent negative peer influence from an early age